Experimental determination of surface emissivity for military equipment components and comparison with reference data - Lazarevic, Lazar; Hristov, Nebojsa; Jerkovic, Damir; Latinkic, Darko; Bučko, Mihael (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: The aim of this paper was to investigate the emissivity of materials relevant to the Serbian Armed Forces and to assess their role in infrared signature management and camouflage performance. Emissivity is a critical parameter influencing the thermal detectability of objects, as surfaces with higher emissivity emit more infrared radiation and thus become more visible to thermal imaging systems.Methods: In this study, emissivity values of textiles, wood, metals, and polymeric components were measured using a FLIR-based thermographic method. The applied approach proved to be fast and reliable, with results consistent with established reference data.Results: Differences between material classes were evident: textiles and polymers generally showed high emissivity, metals displayed lower values strongly affected by surface treatments, while wooden elements remained highly emissive and therefore more exposed to detection. These findings confirm that emissivity is highly dependent on material type, surface finish, and applied coatings.Conclusion: The results provide a comprehensive dataset for military-relevant materials and highlight the practical importance of emissivity characterization in the development of effective camouflage strategies. By integrating accurate emissivity data into infrared signature modeling, it becomes possible to optimize camouflage design and improve operational survivability by reducing the probability of detection on the battlefield.
Keywords: emissivity; infrared thermography; FLIR measurement; military equipment